Memperkuat Ketahanan Nasional: Aktualisasi Bela Negara Melalui Literasi Digital - Rasona Sunara Akbar; Tatang Iskandar; M Aditia Prasetyo; Tiara Okta Damayanti; M Ilham Khomaidi; Miko Dwi Abadi; Safrudin Bachtiar C.R; Ruke Renhard (Journal on Education, 2024)
This research emphasizes the importance of digital literacy in strengthening national resilience and maintaining the nation's sovereignty in the digital era. Using qualitative analysis of secondary data, this research reveals that digital literacy involves effectively using technology and critically understanding and analyzing information. The method used in this research is a qualitative analysis of secondary data that includes regulations, policies, and initiatives related to digital literacy. The results show that digital literacy is essential in improving people's ability to use information and communication technology effectively and in understanding, analyzing, and using information critically to counter propaganda and fake news. The research also emphasizes the importance of integrating digital literacy education in the curriculum, learning programs, development of educational digital content, and related regulations. The study concludes that developing digital literacy programs that are inclusive and accessible to all levels of society is essential to strengthening national resilience.